Determining the Relationship between Employee Engagement and Employee Satisfaction: A Review of Literature (International Journal of Psychosocial Rehabilitation, 2020)
The review paper attempts to review and summarize the existing literature available on employee engagement and employee satisfaction. Employee engagement is viewed as a multi-faceted construct and a unitary construct. Multi-faceted constructs involve cognition, emotions, and behaviors, whereas unitary constructs deal with a positive bent of mind, willingness of the employee, and dedication. Employee satisfaction is also psychological. The paper has shown that a positive and direct relationship exists between the engagement of an employee and his level of contentment with the job, as well as the existence of an indirect relationship between the two.